1993
DOI: 10.1142/s021773239300163x
|View full text |Cite
|
Sign up to set email alerts
|

Parity Violation and the Mean Field Approximation for the Anyon Gas

Abstract: We examine an approach to justifying the mean field approximation for the anyon gas, using the scattering of anyons. Parity violation permits a nonzero average scattering angle, from which one can extract a mean radius of curvature for anyons. If this is larger than the interparticle separation, one expects that the graininess of the statistical magnetic field is unimportant, and that the mean field approximation is good. We argue that a non-conventional interaction between anyons is crucial, in which case the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…To make these ideas concrete, we can examine the case discussed in [10,12], where the potential was parameterized by a phase shift in the lowest partial wave.…”
Section: Generalitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…To make these ideas concrete, we can examine the case discussed in [10,12], where the potential was parameterized by a phase shift in the lowest partial wave.…”
Section: Generalitiesmentioning
confidence: 99%
“…In the latter part of the paper, we applied the "asymmetric-scattering" method discussed in [10] on anyons with a hard-disk repulsion in order to extract a criterion for the validity of the MFA. In agreement with previous works, we found that the statistical interaction must be weak both for anyons near bosons and near fermions, the quantitative criteria being given by (17) and (19).…”
Section: Anyons With Hard-disk Repulsionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent paper [10], another means of justifying the MFA which does not rely on self-consistency was explored. The argument, alluded to in Ref.…”
mentioning
confidence: 99%